2015
DOI: 10.1002/mop.29041
|View full text |Cite
|
Sign up to set email alerts
|

A compact meta‐atom for dual band negative permittivity metamaterial

Abstract: In this letter, a compact design of electric meta‐atom has been proposed as a dual band negative permittivity metamaterial. Compared with the earlier work, the proposed dual band meta‐atom has a better coupling strength at both the resonances and it is also more compact. This dual band design utilizes the mechanism of the resonance coupling between a meander line loaded delta loop meta‐atom and a rectangular close ring meta‐atom. The proposed meta‐atom is designed and investigated by both simulation and experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 15 publications
(27 reference statements)
0
19
0
Order By: Relevance
“…Although square loop resonator has advantage in terms of polarization insensitive behaviour for normally incident wave [29], the disadvantage is regarding single-band response and electrically large size as indicated by very high value of 0 / . The open delta loop resonator (ODLR) proposed by Sabah [30] is shown to have single-band magnetic response for parallelly incident wave, whereas Sarkhel [26] has recently shown electric response for meander-line loaded closed delta loop resonator (CDLR) for normally incident wave. However disadvantage of both designs is that they are highly polarization sensitive.…”
Section: Design and Simulations Of Triple-band Electric Metamaterials mentioning
confidence: 99%
See 4 more Smart Citations
“…Although square loop resonator has advantage in terms of polarization insensitive behaviour for normally incident wave [29], the disadvantage is regarding single-band response and electrically large size as indicated by very high value of 0 / . The open delta loop resonator (ODLR) proposed by Sabah [30] is shown to have single-band magnetic response for parallelly incident wave, whereas Sarkhel [26] has recently shown electric response for meander-line loaded closed delta loop resonator (CDLR) for normally incident wave. However disadvantage of both designs is that they are highly polarization sensitive.…”
Section: Design and Simulations Of Triple-band Electric Metamaterials mentioning
confidence: 99%
“…For comparison, we have considered unit cells operating in microwave regime. From Table 3, it is indicated that, compared to [17,18,20,26], the proposed TBEMR structure exhibits triple-band response and highest value of ( 0 / ) ratio at lower resonant frequency of 4.32 GHz. Moreover at other two resonant frequencies, its value more than 4 is maintained.…”
Section: Effect Of Changing Metallic Strip Widthmentioning
confidence: 99%
See 3 more Smart Citations